Millennial-scale variations of the Holocene North Atlantic mid-depth gyre inferred from radiocarbon and neodymium isotopes in cold water corals. (1st May 2019) - Colin, Christophe; Tisnérat-Laborde, Nadine; Mienis, Furu; Collart, Tim; Pons-Branchu, Edwige; Dubois-Dauphin, Quentin; Frank, Norbert; Dapoigny, Arnaud; Ayache, Mohamed; Swingedouw, Didier; Dutay, Jean-Claude; Eynaud, Frédérique; et al.
Abstract: Variations in North Atlantic Ocean mid-depth circulation during the Holocene are poorly understood. It is believed that they had a significant influence on the properties of water entering the Nordic Sea by redistributing heat and freshwater, potentially affecting deep-water formation and climate. To improve our knowledge of the NE Atlantic mid-depth circulation, radiocarbon and neodymium isotope analyses have been then carried out on precisely dated (U-Th) L. pertusa and M. oculata coral fragments from two sediment cores taken at ∼750 m water depth on the SW Rockall Trough margin. Cold-water coral (CWC) εNd values vary between −12.2 ± 0.3 and −16.6 ± 0.4 and result from variable contributions of unradiogenic mid-depth subpolar gyre (mid-SPG) water (∼-15) and more radiogenic Eastern North Atlantic Water (ENAW) (∼-11) which is transported northward to the Rockall Trough by boundary currents along the European margin. Increased coral εNd reflects a westward contraction of the mid-SPG water and a higher proportion of ENAW. The mid-Holocene (from 8.8 to 6.8 ka BP) is marked by unradiogenic coral εNd (from −16.6 ± 0.4 to −14.6 ± 0.5) indicating a greater eastward extension of the mid-SPG. This is followed by a shift from 6.8 to 5 ka BP toward more radiogenic εNd values (from −15.4 ± 0.3 to −13.3 ± 0.2) suggesting a westward contraction of the mid-SPG and a higher proportion of ENAW. The mid-Holocene long-term change in εNd is characterized by millennial variations of up to 2.5 epsilon units well marked during the Late Holocene, indicating that eastward extension of the mid-SPG coeval with warm periods in northern Europe (e.g. the Medieval Climatic Anomaly and the Roman Warm Period). Most of the CWC-derived Δ 14 C values match the global ocean values indicating that the water masses bathing the corals were generally well ventilated; the exceptions are a few short intervals of eastward extension of the mid-SPG, which are characterized by lower Δ 14 C during the late Holocene. We propose that these minor Δ 14 C fluctuations in the Rockall Trough may be related to local changes in the mixed layer depth or to variability in the advection of water from the Labrador Sea where deep convection gives rise to thermocline waters that are relatively depleted in terms of Δ 14 C. The eastward extension of the mid-SPG between 8.8 and 6.8 ka BP is associated with the Holocene climatic optimum, concurrent with a maximum strength of the Iceland-Scotland Overflow Water (ISOW), which is indicative of an increase in the Atlantic Meridional Overturning Circulation (AMOC). This period is followed by a transition in the North Atlantic circulation, which occurred around 6.8 ka BP, and coincides with the onset of Labrador Sea Water formation, a decrease of the ISOW strength and a contraction of the mid-SPG leading to a greater intrusion of saline subtropical water into the subpolar Atlantic. Highlights: 1/First detailed record of εNd and Δ 14 C at the SW Rockall Trough during the Holocene. 2/Reconstruction of the mid-depth sub-polar gyre (mid-SPG) intensity during the Holocene. 3/Evidence of a progressive mid-Holocene re-organization of the mid-depth circulation. 4/Evidence of a link between millennial variations in the SPG intensity and climate.